PRODUKTIVITAS KERJA PEGAWAI YANG DI PENGARUHI OLEH WORK FROM HOME (WFH) DAN LINGKUNGAN KERJA SELAMA MASA PANDEMI PADA DINAS PERHUBUNGAN KOTA BIMA - Al Halim, Rifky; Kusumayadi, Firmansyah (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the partially significant effect of work from home (WHF) on workproductivity at the Bima City Transportation Service. To find out the partially significant effectof the work environment on work productivity at the Department of Transportation of the Cityof Bima. To find out (WHF) and the work environment have a significant simultaneous effecton the work productivity of employees at the Department of Transportation of the City of Bima.The instrument in this study used a questionnaire with a Likert scale. The population in thisstudy were 80 employees consisting of 34 civil servants and 46 honorary employees. Thesample in this study were 34 civil servants. The sampling technique used by the researcherwas purposive sampling. Data collection techniques using questionnaires, observation andliterature studies, data analysis techniques using validity tests, reliability tests, classicalassumptions test, multiple linear regression analysis, correlation analysis, coefficient ofdetermination, t test and f test with the help of SPSS. The results showed that Work FromHome (WFH) significantly affected employee productivity at the Department of Transportationof the City of Bima, the work environment significantly had an influence on the productivity ofemployees at the Department of Transportation of the City of Bima, simultaneously thevariables (X1) Work From Home (WFH) and the work environment (X2) at the Department ofTransportation of the City of Bima has a significant effect on employee work productivity (Y)